Methanol production from cattle feedlot manure - Bareno, Jocelyn D. (College of Engineering, 1980)
Plant capacity: 525 tons (476.3 MT) of 99.85% CH3OH per day -- Plant area: 208,884 sq.ft. (19,405 sq.m.) -- Plant location: Bukidnon, Northern Mindanao -- Total fixed capital investment: P 1,641,864,200 per year -- Operating cost at max. production: P 2,861,167,840 per year -- Annual sales at max. production: P 7,048,574,495 per year -- Return on investment: 12.75% -- Pay-out time: 4.7 years -- Break-even point: 27% of max. production